2012
DOI: 10.1002/pssa.201127538
|View full text |Cite
|
Sign up to set email alerts
|

Multiangle combined magnetic‐field annealing of Co‐based amorphous microwires for sensor applications

Abstract: The effect of multiangle combined magnetic-field annealing (MCMFA) on the GMI performance of melt-extracted Cobased amorphous microwires for sensor applications is studied using a precision impedance analyzer. Experimental results indicated that MCMFA treatment can effectively improve the GMI effect comparing with as-cast and conventional vacuumannealed (CVA) wires. The maximum GMI ratio [DZ/Z max ] max and field response sensitivity j max of transverse combined magnetic-field annealed (TCMFA, a ¼ 908) wires c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…More importantly, according to the formula (3), the larger φ caused by the action of high magnetic field it is, the huger magnetic energy E is, which is consistent with the total magnetic moment variation along the field direction in a unit volume in Ref. . Finally, the surface of cluster fibers in transverse magnetization direction generates negative and positive magnetic charges that are arranged regularly and alternatively, the alternative arrangement of charges satisfy the principle of energy minimization, and what's more, induce the changes of isothermal magnetic entropy and magnetic energy caused by high magnetic field energy and thermal activation.…”
Section: Resultssupporting
confidence: 69%
“…More importantly, according to the formula (3), the larger φ caused by the action of high magnetic field it is, the huger magnetic energy E is, which is consistent with the total magnetic moment variation along the field direction in a unit volume in Ref. . Finally, the surface of cluster fibers in transverse magnetization direction generates negative and positive magnetic charges that are arranged regularly and alternatively, the alternative arrangement of charges satisfy the principle of energy minimization, and what's more, induce the changes of isothermal magnetic entropy and magnetic energy caused by high magnetic field energy and thermal activation.…”
Section: Resultssupporting
confidence: 69%
“…Also the regular and closed surface circumferential magnetic domains essentially promoted circumferential anisotropy and permeability thus increased maximum of Z, this is the mechanism of enhancement of GMI ratio by ADA process. Generally, there exist so many appropriate annealing treatments, which can improve both GMI and magnetic properties of as-fabricated wires to some extent, such as conventional vacuum annealing (VA), magnetic-field annealing (MA) [5] and conventional Joule annealing (CJA) [30]. According to previous reports, it has been confirmed that conventional JA could work better than VA and MA because of the generating circular magnetic field induced by the electricity current of CJA can enhance circumferential magnetic anisotropy for a wire-shaped sample further to increase its magneto-impedance ratio and field response [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…Co-based amorphous wires with excellent giant magneto-impedance (GMI) properties have recently attracted much attention due to their potential applications, especially as GMI sensor elements for detecting very slight magnetic fields [1][2][3][4][5]. The principal source of GMI effect is accordingly ascribed to the typical skin effect, which means AC current flows only in the outer region of the magnetic materials at relatively higher frequency.…”
Section: Introductionmentioning
confidence: 99%
“…First strategy involves designing new magnetic materials with the desired magnetic and magnetoimpedance properties while second focus on improving the magnetic and magnetoimpedance properties of existing materials, through advanced annealing techniques including stress-jouleannealing [7] or the recently reported multi-angle annealing techniques [8]. A relatively novel approach to tailoring the magnetic response of magnetic wires is using the effect of magnetostatic interaction between them [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%